PENGARUH SIKAP PROFESIONAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMA MUHAMMADIYAH 1 PONOROGO - Nayni Nayni; Adi Santoso; Eka Destriyanto Pristi Ayuningtyas (STIE Trisna Negara OKU Timur, 2023)
The purpose of this research is to find out whether there is an influence of professional attitude (x1) on teacher performance (y), the effect of work motivation (x2) on teacher performance (y), the effect of work discipline (X3) on teacher performance and to find out how much the influence of professional attitude (x1), the need for work motivation (x2) and work discipline (x3) jointly affect teacher performance (y). The method used in this study is the observation method, with a quantitative correlation and regression approach. The number of samples is 45 people taken from the teaching staff at SMA Muhammadiyah 1 Ponorogo. The data processing method uses multiple regression analysis. The results showed that the professional attitude variable (x1) had a significant influence on teacher performance (y) as evidenced by the coefficient of professional attitude variable (x1) with a t-test value of 3.225 > ttable 2.019, while the work motivation variable (x2) with a test value tcount is 3.924 which is greater than ttable 2.019, while the work discipline variable (x3) has a tcount test value of 3.583 > 2.019. Based on the f test shows that the probability value is <0.05, it can be said that there is a jointly significant influence between the independent variables on the dependent variable. This means that there is a positive influence between professional attitude (x1), work motivation (x2), work discipline (x3) on teacher performance (y). teacher performance. Based on the results of the analysis it can be concluded that together professional attitude, work motivation and work discipline have a significant positive influence on the performance of SMA Muhammadiyah 1 Ponorogo teachers.Keywords: teacher performance, professional attitude, work motivation and work discipline